Readers’ Responses to The Reading of Translations of Children’s Story - Engliana Engliana; Adityaratri Indrapratiwi; Raden Mas Ransang (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
The goals of this paper are to seek the readers’ reactions, having gone through the two versions of English-to-Indonesian translations of children’s short story, and to explain the readers’ reactions to the two versions of the translations. The interview questions focus on the loanword or borrowing translation strategies employed by the student translators. Ten parents with children volunteered to read and respond to translation reading. The results show that the readers thought it would be better for the translators not to apply the borrowing procedure in translating children’s stories as it will hinder the meanings resulting in an uneasy feeling of reading the story to their children. Keywords: reader reaction, children story translation, borrowing, equivalence.